(untitled) (Architecture Image Studies, 2025)
This study investigates the influence of leadership style, human capital, and job analysis on organizational performance, with strategic planning serving as a mediating variable within the local government of South Buton Regency, Indonesia. Using a quantitative explanatory approach, data were obtained from 148 respondents across 37 regional government work units. Structural Equation Modeling was applied to analyze direct and indirect causal effects. The findings reveal that leadership style and job analysis significantly enhance organizational performance, whereas human capital shows a positive but insignificant direct impact. Strategic planning significantly mediates the relationships between leadership style and job analysis with organizational performance, but not that of human capital. These results emphasize the importance of adaptive leadership, competency-based job structuring, and systematic strategic planning as drivers of public-sector performance. The study offers theoretical contributions to public administration literature and practical implications for strengthening governance capacity in newly autonomous regions.